Analysis of Power Outages in Kabale Town: A Case Study of 33 KV Mbarara North-Kabale West Feeder. - Atibuni, Yofat (Kabale University, 2025)
This project examined the 33kV Mbarara North-Kabale feeder, a vital power supply line for Kabale Town, to address the persistent power outages affecting the region. The primary objectives were to evaluate the existing feeder infrastructure, analyze outage data, and propose solutions to minimize these disruptions. Spanning 145 km, the feeder traverses challenging environmental and geographical terrain, contributing to infrastructure stress and reliability concerns. The study included a comprehensive analysis of the feeder's infrastructure and load characteristics. A load flow assessment highlighted issues such as voltage fluctuations, significant power losses, and points of failure stemming from aged or insufficient equipment. Outage data revealed technical challenges, including surge arrestor failures, broken jumpers, damaged poles, and improper fuse ratings. Faulty surge arrestors were unable to clear faults, and over-sagging conductors posed risks of low-voltage and high-voltage contact. Environmental factors further exacerbated these problems, with tree cutting in Kyobugombe and Ndija, forested areas in Maziba, deteriorating poles in Katinda, and frequent lightning in Rubaya causing line faults and prolonged outages. To mitigate these issues, the study proposed several technical and operational interventions. These included upgrading surge protection devices, replacing degraded infrastructure, enhancing tree trimming and vegetation control, and ensuring the availability of correctly rated fuses in the Ugandan market. Additional recommendations involved improving the functionality of Automatic Voltage Regulators (AVRs) and Ground Voltage Regulators (GVRs) to stabilize voltage along the feeder.